Nutrient and Physiological Requirements for Biomass Production of Pestalotiopsis sp. UMAS P14 and Pseudopestalotiopsis sp. UMAS P2005/2592 - Lateef, A.A.; Sepiah, M.; Mohamad Hasnul., B (Universiti Malaysia Sarawak (UNIMAS), 2016)
Fungi are important decomposers in our ecosystem and are useful in metabolite production, bio-degradation and bio-sorption of different substrates and wastes through their mycelial biomass. Fungal species are known to have different preferences for their growth requirements. Two fungal species Pestalotiopsis and Pseudopestalotiopsis useful in many biotechnological applications were studied. Nutrient and physiological requirements for mycelial biomass production such as carbon and nitrogen, pH, light and temperature were investigated. Both fungal isolates were grown in liquid basal medium supplemented separately with various carbon and nitrogen source and incubated under different light, pH and temperature conditions for 15 days. In general, Pestalotiopsis sp. and Pseudopestalotiopsis sp. showed significant preferences for monosaccharide and disaccharide carbon source as compared to sugar alcohols and polysaccharides, whereas ammonium tartrate was more preferred as a nitrogen source compared to ammonium nitrate, ammonium sulphate and other ammonium salts. These two fungal species were able to grow and produce good mycelial biomass (223.33 mg for Pseudopestalotiopsis and 136.67 mg for Pestalotiopsis) at temperature range of 15°C to 30°C and (290.00 mg for Pseudopestalotiopsis and 256.67 mg for Pestalotiopsis) on media pH of slightly acidic to slightly alkaline. However, they showed no significant preferences between constant light, total darkness and alternate light conditions. The results from this study will be very useful for the mycelial biomass production of Pestalotiopsis sp. and Pseudopestalotiopsis sp. for their biotechnological applications.